"I Was Once Independent": The Southern Seal Protest and Inuit - Wenzel, George (Anthropologica, 2022)
On three occasions in the past 20 years, the anti-sealing/animal rights movement has initiated protests which have progressively damaged one of the traditional mainstays of Inuit adaptation, the hunting of ringed seals (Phoca hispida). While the stated objective of these protests was control of the commercial exploitation of harp seals (Pagophilus groenlandicus) along the Atlantic coast of Canada, they have eroded the ability of Canadian Inuit to exploit a key traditional resource. This paper is a preliminary examination of the nature and consequences of two levels of ongoing conflict over sealing between Inuit seal users and southern seal protectors. The first level of conflict is the economic dimension whereby, under cash market conditions that have existed since the end of World War II, Inuit in parts of the Canadian Arctic have developed their local economic base on the sale of ringed sealskins. The second level of conflict involves social and cultural penalties incurred by Inuit under present conditions.